AB1149 Biologics in the management of pediatric autoimmune and autoinflammatory diseases: Side effects. (23rd January 2014) - Russo, G.; Forni, C.; Scotti, N.; Carlomagno, R.; Alessio, M.
Abstract : Background: The last 20 years have seen an evolution in the approach to therapy of many chronic pediatric diseases such as autoimmune, cardiological, neoplastic and infectious disorders. However, persisting treatment failures lead to the development of a new class of drugs—biologicals—which have been used to target specific cytokines and receptors thought to be pivotal in the perpetuation of inflammation. So, there are few studies of efficacy or safety of these new biologicals in this vulnerable population. Objectives: to summarize the information available on the efficacy and risks of available biologicals in rheumatic disorders. Methods: In this study, we analyze the adverse reactions described in 57 patients, affected by autoimmune diseases, treated with biologic response modifiers, during the period from 2000 through 2011, in the Pediatric Rheumatology Unit of the Federico II University in Naples. 5 patients (8, 8%) presented autoinflammatory diseases and 52 children (91, 2%) were affected by juvenile idiopathic arthritis, in particular poliarthritis (31/52, 59, 6%), oligoarthritis (13/52, 25%) and systemic type (8/52, 15.4%). These patients were treated withinfliximab (anti-TNF-monoclonal antibody, Remicade: 5/57), etanercept (soluble TNF receptor fusion protein, Enbrel: 53/57), adalimumab (anti-TNF-monoclonal antibody, Humira: 12/57), anakinra (interleukin-1 receptor antagonist, Kineret: 5/57) and Abatacept (anti-CTLA4 fusion protein: 4/57). Some patients received different biologics, so the number of biologics was finally 79. Results: Toxicities occurred during etanercept therapy in 5 patients (9, 4%): optic neuritis (2 cases), Candida Albicans esophagitis (1), anaphylactic shock (1) and Crhon's disease (1). Adverse events were described in 3/5 patients treated with infliximab (60%): anaphylactic shock (2) and defluvium (1). We also specify that the two patients with optic neuritis and Candida Albicans esophagitis during Etanercept therapy presented also defluvium and anaphylactic shock with infliximab. We didn't observe adverse effects during the other biologic therapies. Then, chickenpox affected two patients treated with etanercept, without any complications. Finally, our patients presented toxicities in 10.1% of cases (8/79), respectively with Etanercept (5/79: 6, 3%) and Infliximab (3/79: 3, 8%). Conclusions: Biologic drugs present remarkable advantages in terms of disease control for children, especially in those whose disease cannot be controlled with conventional therapies, but their risks are still being assessed. Because these biologic response modifiers are monoclonal antibodies or receptor fusion proteins against proinflammatory cytokines and are potent inhibitors for excessive reactions as well as physiological reactions, appropriate use of these agents requires clinical expertise and experience. Our data regarding biologic use in children suggest that they are well tolerated and relatively safe. Adverse reactions are infrequent in the short term, but loss of response is a long-term problem, particularly in children. More information is needed about very long term risks. Further collection of data on these agents is still needed, but this should not restrict access to these agents for children in whom no other agent is effective. Disclosure of Interest: None Declared